Language MOOCs. Providing Learning, Transcending Boundaries - Martín-Monje, Elena (De Gruyter, 2015)
Language MOOCs (or LMOOCs) are dedicated Web-based online courses for second languages with unrestricted access and potentially unlimited participation. They are generating interest and expectation in the contexts of university education, lifelong learning and online training in general. This pioneering book presents an initial analysis of the theoretical and methodological issues underlying LMOOCs and presents empirical evidence of their potential for the development of language communicative competences, based upon previously unpublished research. It provides a mosaic-like view of LMOOC research, not only with respect to the geographical and institutional origin of its authors, but also to the heterogeneous nature of their respective academic backgrounds, and suggests directions for future development. As in other types of online language courses, the integration of the results of multidisciplinary research projects and teaching experiences related to LMOOCs is fundamental to make the field advance steadily and respond to some of the real challenges and problems faced by individuals working and living in competitive plurilingual societies today.